Form-meaning links in the development of visual word recognition. - Nation, K (2009)
Learning to read takes time and it requires explicit instruction. Three decades of research has taught us a good deal about how children learn about the links between orthography and phonology during word reading development. However, we have learned less about the links that children build between orthographic form and meaning. This is surprising given that the goal of reading development must be for children to develop an orthographic system that allows meanings to be accessed quickly, reliably and efficiently from orthography. This review considers whether meaning-related information is used when children read words aloud, and asks what we know about how and when children make connections between form and meaning during the course of reading development.